Top-up safety simulations for the diamond storage ring - Martin, I; Bailey, C; Bartolini, R; Longhi, E; Walker, R (European Physical Society Accelerator Group (EPS-AG), 2008)
To ensure that it is not possible for a train of injected electron bunches to pass down an open beam-line during top-up operation at the Diamond Light Source, an extensive program of tracking studies has been performed. Various error scenarios have been investigated, with realistic magnetic field, trajectory, aperture and energy errors all taken into account. We describe the tracking methods used, scenarios considered and the interlocks required in order to maintain safety during top-up operation.